Assessing Nerve Block and Opioid Analgesics on Anxiety and Depression in Patients with Lumbar Radiculopathy - Ashley Deng; Liying Wei; Eduardo Espiridion (International Journal of Pain, 2025)
Background : Lumbar radiculopathy, marked by radiating lower back pain and neurological deficits, is often complicated by psychological comorbidities such as anxiety and depression. While nerve blocks and opioid analgesics are common treatments, their comparative effects on mental health outcomes remain unclear. Methods : This study examines the impact of nerve blocks versus opioids on the development of anxiety and depression in patients with lumbar radiculopathy using the TriNetX database. Two matched cohorts of adult patients (n = 48,936 each) were identified based on treatment type: nerve blocks or opioid analgesics. Propensity score matching accounted for demographics, comorbidities, and medication history. Odds ratios (OR) and hazard ratios (HR) were calculated to assess the incidence and time-to-onset of anxiety (ICD-10 F41.9) and major depressive disorder (ICD-10 F33). Results : The nerve block group had significantly lower odds of developing anxiety (OR: 0.401, 95% CI: 0.384-0.418) and depression (OR: 0.542, 95% CI: 0.506-0.581) compared to the opioid group. Time-to-event analysis further showed decreased hazard ratios for anxiety (HR: 0.554, 95% CI: 0.532-0.577, P = 0.026) and depression (HR: 0.741, 95% CI: 0.692-0.794, P < 0.001) in the nerve block cohort. Conclusions: These findings suggest nerve blocks may lower the risk and delay the onset of anxiety and depression in lumbar radiculopathy, highlighting their potential mental health advantages over opioids. Future studies should explore integrative pain management approaches that prioritize both physical and psychological well-being.